Presente y futuro de los trabajadores autónomos a partir del contenido de la Ley 20/2007, del Estatuto del Trabajo Autónomo - Landaburu Carracedo, María José (REVESCO. Revista de Estudios Cooperativos, 2009)
The target of the present work is to analyze the juridical basis introduced across the Law 20/2007 in the ambience of the autonomous work, emphasizing his original and innovation both in Spain and in the ambience of the European Union, where doesn’t exist a similar precedent in juridical terms to the legislative innovation with which we are dealing. From this point of view, the content of the norm is analyzed, focusing on the rules established legally to determine the subjective ambience of application of the same one, the notes of the professional basis of the autonomous worker established in the Law and the concept and juridical basis applicable to the new juridical figure created by the Law under the denomination of economically dependent autonomous worker. Likewise, the work deals with establishing some hypotheses about its perspectives of future from the impulse caused by the promulgation of that norm and challenges which have those who exercise the autonomous work.